The impact of air pollution on the stock performance: Evidence from China new energy vehicle industry - Haoran Xu; Yanjie Chen (Energy Reports, 2022)
With Tesla stock soaring up into the sky with one start, people’s attention is once again focused on the new energy vehicle (NEV) industry. Based on China’s new energy vehicle market, we explore the reason behind of soaring stock price from the perspective of the interaction between return on stocks and the environmental changes. We use a fixed effect regression model to estimate the impact of air pollution on the stock performance of the new energy vehicle industry. We find that deteriorative air quality leads to a positive average stock return of NEV firms.